Human periventricular grey somatosensory evoked potentials suggest rostrocaudally inverted somatotopy. - Pereira, E; Wang, S; Owen, S; Aziz, T; Green, A (2013)
BACKGROUND: Somatosensory homunculi have been demonstrated in primary somatosensory cortex and ventral posterior thalamus but not periaqueductal and periventricular grey matter (PAVG), a therapeutic target for deep brain stimulation (DBS) in chronic pain. AIMS: The study is an investigation of somatotopic representation in PAVG and assessment for a somatosensory homunculus. METHODS: Five human subjects were investigated using electrical somatosensory stimulation and deep brain macroelectrode recording. DBS were implanted in the contralateral PAVG. Cutaneous arm, leg and face regions were stimulated while event-related potentials were recorded from deep brain electrodes. Electrode contact positions were mapped using MRI and brain atlas information. RESULTS: Monopolar P1 somatosensory evoked potential amplitudes were highest and onset latencies shortest in contralateral caudal PAVG with facial stimulation and rostral with leg stimulation, in agreement with reported subjective sensation during intra-operative electrode advancement. CONCLUSIONS: A rostrocaudally inverted somatosensory homunculus exists in the human PAVG region. Objective human evidence of PAVG somatotopy increases understanding of a brainstem region important to pain and autonomic control that is a clinical target for both pharmacological and neurosurgical therapies. Such knowledge may assist DBS target localisation for neuropathic pain syndromes related to particular body regions like brachial plexopathies, anaesthesia dolorosa and phantom limb pain.